Experimental investigation of fluid loss and cake thickness control ability of zirconium (IV) oxide (Z_R O_2) nanoparticles in water based drilling mud. - Paul, Anawe A. L.; Adewale, Folayan J. (International Journal of Engineering and Technology, 2018)
A major technical and economical concern of the oil well drilling industry is the potential damage to productive formations because of excessive drilling fluid filtration and its multiplier effect on cake thickness. High fluid loss (high cake permeability) results in thick filter cake which reduces the effective diameter of the hole (tight holes) and causes various problems such as excessive torque when rotating the pipe, excessive drag when pulling it and high swab and surge pressures due to reduced hole diameter and differential pipe sticking due to increase in pipe contact.It is in this light that the potential of Zirconium (IV) oxide (Z_r O_2) nanoparticles in combating excessive filtration problem in Water Based Mud was investigated. Preliminary results show that addition of 0.50g (Z_r O_2) nanoparticle concentration brought about 19.10% reduction in fluid loss and 14.29 % reduction in cake thickness for the High Temperature/ High Pressure (HPHT) filtration test at 500psi and 250 OF. Similarly, the highest reduction of 48.31% and 38.10% in fluid loss and cake thickness respectively was achieved with addition of an optimum concentration of 2.0g of (Z_r O_2) nanoparticles for the HTHP filtration test at the same temperature and pressure.
Keywords: Cake Permeability; Fluid Loss; HTHP; Nanoparticles; Water Based Mud (WBM); Zirconium (IV) Oxide.